Advanced .NET Remoting, Second Edition - Rammer, Ingo (Apress, 2012)
In the time since the first edition of this book has been published, quite a bit has changed in the world of software development on Microsoft’s platforms. The .NET Framework has become a tried-and-true development platform, and service orientation gained a larger-than-expected momentum. The latter especially presents a very challenging task for the developer using .NET Remoting: the need to avoid possible incompatibilities with future paradigms. If service orientation will, in the next few years, gain the success it deserves, it might be important for your application to be developed in a way to easily adopt these new ideas. In this book, I have therefore followed a slightly different approach from the one I did in the previous edition. While the first book focused only on covering all the features of the .NET Remoting framework, Mario and I tried to extend this second edition with the best practices for using this technology. While it still covers nearly each and every feature of the .NET Remoting framework, the largest part of the new chapters of this book—especially Chapters